Automated deduction in geometry : 10th International Workshop, ADG 2014, Coimbra, Portugal, July 9-11, 2014, Revised selected papers /: 10th International Workshop, ADG 2014, Coimbra, Portugal, July 9-11, 2014, Revised selected papers. (2015) - Unknown
No abstract available